Active human nucleolar organizer regions are interspersed with inactive rDNA repeats in normal and tumor cells. (June 2015) - Zillner, Karina; Komatsu, Jun; Filarsky, Katharina; Kalepu, Rajakiran; Bensimon, Aaron; Németh, Attila
Aim: The synthesis of rRNA is a key determinant of normal and malignant cell growth and subject to epigenetic regulation. Yet, the epigenomic features of rDNA arrays clustered in nucleolar organizer regions are largely unknown. We set out to explore for the first time how DNA methylation is distributed on individual rDNA arrays.Materials & Methods: Here we combined immunofluorescence detection of DNA modifications with fluorescence hybridization of single DNA fibers, metaphase immuno-FISH and methylation-sensitive restriction enzyme digestions followed by Southern blot.Results: We found clustering of both hypomethylated and hypermethylated repeat units and hypermethylation of noncanonical rDNA in IMR90 fibroblasts and HCT116 colorectal carcinoma cells. Surprisingly, we also found transitions between hypo- and hypermethylated rDNA repeat clusters on single DNA fibers.Conclusion: Collectively, our analyses revealed co-existence of different epialleles on individual nucleolar organizer regions and showed that epi-combing is a valuable approach to analyze epigenomic patterns of repetitive DNA.